Acute effect of Clitoria ternatea flower beverage on glycemic response and antioxidant capacity in healthy subjects: a randomized crossover trial - Charoonsri Chusak; Thavaree Thilavech; Christiani Jeyakumar Henry; Sirichai Adisakwattana (BMC, 2018)
Abstract Background Clitoria ternatea L., a natural food-colorant containing anthocyanin, demonstrated antioxidant and antihyperglycemic activity. The aim of this study was to determine the effects of Clitoria ternatea flower extract (CTE) on postprandial plasma glycemia response and antioxidant status in healthy men. Methods In a randomized, crossover study, 15 healthy men (ages 22.53 ± 0.30 years; with body mass index of 21.57 ± 0.54 kg/m2) consumed five beverages: (1) 50 g sucrose in 400 mL water; (2) 1 g CTE in 400 mL of water; (3) 2 g CTE in 400 mL of water; (4) 50 g sucrose and 1 g CTE in 400 mL of water; and (5) 50 g sucrose and 2 g CTE in 400 mL of water. Incremental postprandial plasma glucose, insulin, uric acid, antioxidant capacities and lipid peroxidation were measured during 3 h of administration. Results After 30 min ingestion, the postprandial plasma glucose and insulin levels were suppressed when consuming sucrose plus 1 g and 2 g CTE. In addition, consumption of CTE alone did not alter plasma glucose and insulin concentration in the fasting state. The significant increase in plasma antioxidant capacity (ferric reducing ability of plasma (FRAP), oxygen radical absorbance capacity (ORAC), trolox equivalent antioxidant capacity (TEAC), and protein thiol) and the decrease in malondialdehyde (MDA) level were observed in the subjects who received 1 g and 2 g CTE. Furthermore, consumption of CTE protected sucrose-induced reduction in ORAC and TEAC and increase in plasma MDA. Conclusions These findings suggest that an acute ingestion of CTE increases plasma antioxidant capacity without hypoglycemia in the fasting state. It also improves postprandial glucose, insulin and antioxidant status when consumed with sucrose. Trial registration Thai Clinical Trials Registry: TCTR20170609003 . Registered 09 September 2017. 'retrospectively registered'.